Teori Pembangunan Dunia Ketiga Dan Pengaruhnya Terhadap Pembangunan Nasional - Rahayu Sulistiowati (PUBLICA, 2011)
In which way world development theory of globalization influence towards national development strategy in Indonesia become principal topic here. Fact that at this world, there is no country genuinely autonomous, that mean there is no country which development perceivable only as reflection from what is going on outside the national limits, all countries mutual depend on each other. One clear dimension from that interdepende, brainstorming has physical, biological and ecological hit overall and limitedness. Conjunction with the problem above, so its follow three things that become series of the key issue, which are: (a) money current and investment pattern; (b) technology change and production internationalizing; (c) trade and international regime. From all of that third keys issue, for Indonesia in the effort of choose and carry out the develpment strategy must pay attention external factors besides internal factors. Mainstream that mus can be built in this situation and condition now days, is how to create and give birth to innovative thingking, strategic and application so that efficiency and effective the result.